ANALISIS PENYELESAIAN SENGKETA TANAH ANTARA PT PERTIWI LESTARI DENGAN PETANI DI TELUK JAMBE DI KABUPATEN KARAWANG BERDASARKAN UNDANG -UNDANG NO 21 TAHUN 1961 TENTANG PENCABUTAN HAK ATAS TANAH - Putra, Renndy Yusak; Kurniati, Grasia (Jurnal Ilmiah Wahana Pendidikan, 2024)
Land is utilized and used for the prosperity of society physically and spiritually, the condition is to maintain its sustainability. Based on Article 4 paragraph (1) of Law Number 5 of 1960 concerning Basic Agrarian Regulations, it states that land in a juridical sense is the surface of the earth, which includes the surface of the earth that is on land and the surface of the earth that is under water, the sea. Article 4 of Law Number 5 of 1960 basically regulates the meaning of rights to land, which includes the surface of the earth, which can be applied to the granting of rights underground and in the airspace. This empirical normative legal research method is basically a normative legal approach with the addition of various empirical elements. The land dispute between PT Pertiwi Lestari and residents and Perhutani originated from the developer company's claim over 791 hectares of land in the West Telukjambe area. The ownership claim was based on ownership of a Building Use Rights certificate issued by the Karawang Land Office in 1998. Namely HGB certificate No. 5 village Margamulya, HGB certificate No. 11 Wanajaya village and HGB certificate No. 30 Wanajaya village. According to article 18 of the Basic Agrarian Law, in the public interest, including the interests of the nation and the State as well as the common interests of the people, land rights can be revoked, by providing appropriate compensation and in a manner regulated by law.